1989
DOI: 10.2337/diab.38.10.1258
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hemodynamic and Vascular Albumin Filtration Changes in Diabetic Rats by Aldose Reductase Inhibitors

Abstract: This study investigated hemodynamic changes in diabetic rats and their relationship to changes in vascular albumin permeation and increased metabolism of glucose to sorbitol. The effects of 6 wk of streptozocin-induced diabetes and three structurally different inhibitors of aldose reductase were examined on 1) regional blood flow (assessed with 15-microns 85Sr-labeled microspheres) and vascular permeation by 125I-labeled bovine serum albumin (BSA) and 2) glomerular filtration rate (assessed by plasma clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
4
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(69 citation statements)
references
References 0 publications
9
55
4
1
Order By: Relevance
“…While our group and others have reported that there is a decrease in RBF in diabetic animal models and in patients with Type 1 diabetes [8,9,10,11], other groups have reported that diabetes increases RBF [44,45,46]. The different results from these groups could be related to the methodologies used (video fluorescein angiography and laser Doppler velocimetry), the duration of diabetes, whether or not clinically observable diabetic retinopathy was present, the blood glucose levels at the time of the measurement, and the level of glycaemic control or haemoglobin A 1c in the studied patients [20,47].…”
Section: Discussionmentioning
confidence: 54%
“…While our group and others have reported that there is a decrease in RBF in diabetic animal models and in patients with Type 1 diabetes [8,9,10,11], other groups have reported that diabetes increases RBF [44,45,46]. The different results from these groups could be related to the methodologies used (video fluorescein angiography and laser Doppler velocimetry), the duration of diabetes, whether or not clinically observable diabetic retinopathy was present, the blood glucose levels at the time of the measurement, and the level of glycaemic control or haemoglobin A 1c in the studied patients [20,47].…”
Section: Discussionmentioning
confidence: 54%
“…Since then numerous experimental studies have been carried out to test this hypothesis. These experimental studies of activation of the polyol metabolic pathway and its role in the diabetes-associated renal alterations have so far not given any conclusive results [16][17][18][19][20][21][22]. Some of the inconsistencies in results might be attributed to differences in the severity of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In studies where an effect of aldose reductase inhibitors (ARI) on renal haemodynamics was noticed, typical renal effects of diabetes, e.g. kidney enlargement and/or hyperfiltration were generally absent or not very prominent indicating that the state of diabetes was very mild [16][17][18]. In addition, the causal relationship between increased polyol metabolism and the level of hyperperfusion was difficult to evaluate in these studies since data on renal tissue sorbitol content were not available.…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is linked to increased flux through the polyol or hexosamine pathways which is associated with subsequent alterations in the redox state of pyridine nucleotides. 37 Accumulation of sorbitol in retinal cells is dependant on the activity of aldose reductase and this may impinge on a range of pathways and contribute to diabetic retinopathy. 38 Also de novo synthesis of diacylglycerol (DAG) leading to the over-activation of several isoforms of protein kinase C (PKC), 39 excessive production of free radicals leading to oxidative stress, 40,41 changes in blood rheology and haemodynamics, 42,43 and over-activation of the renin-angiotensin system 44 contribute significantly to retinopathy as diabetes progresses.…”
Section: Retinal Hypoperfusion In Diabetes: Links To Early Pathologymentioning
confidence: 99%